2011
DOI: 10.1097/ccm.0b013e31820eb774
|View full text |Cite
|
Sign up to set email alerts
|

The effect of l-alanyl-l-glutamine dipeptide supplemented total parenteral nutrition on infectious morbidity and insulin sensitivity in critically ill patients*

Abstract: Total parenteral nutrition supplemented with alanine-glutamine in intensive care unit patients is associated with a reduced rate of infectious complications and better glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
7

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 34 publications
2
65
1
7
Order By: Relevance
“…[87][88][89] In contrast, nutrition strategies, such as supplementation of PN with glutamine and the administration of low calorie PN, may reduce development of SH during critical illness. 90,91 In turn, SH can affect delivery of nutrition during critical illness in a variety of ways. Stress hyperglycemia may influence the ability to provide consistent or adequate EN during critical illness.…”
Section: Prolonged Immobility and Stress Hyperglycemiamentioning
confidence: 99%
“…[87][88][89] In contrast, nutrition strategies, such as supplementation of PN with glutamine and the administration of low calorie PN, may reduce development of SH during critical illness. 90,91 In turn, SH can affect delivery of nutrition during critical illness in a variety of ways. Stress hyperglycemia may influence the ability to provide consistent or adequate EN during critical illness.…”
Section: Prolonged Immobility and Stress Hyperglycemiamentioning
confidence: 99%
“…Grau et al (31) studied the effect of alanine-glutamine dipeptide supplemented TPN on incidence of nosocomial infections and found that TPN supplemented with alanine-glutamine in ICU patients is associated with reduced occurence rate of infectious complications. Although glutamine seems to have an effect on the immune system, antioxidant status and glucose metabolism, the benefit of exogenous glutamine on morbidity and mortality is not universally accepted (32).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in studies conducted after the 2000s, the addition of glutamine to the nutritional solutions of patients in critical care or undergoing surgery was shown to reduce the rates of infectious complications and mortality (38)(39)(40)(41). These studies were conducted on homogeneous groups of patients.…”
Section: Glutaminementioning
confidence: 99%